The Effectiveness of Administrative Efforts in Reducing State Administration Disputes - Ahmad Siboy; Sholahuddin Al-Fatih; Virga Dwi Efendi; Nur Putri Hidayah (Lembaga Contrarius Indonesia, 2022)
Regulating administrative efforts as the mandatory procedure is expected to be able to filter and reduce the number of disputes that must be tried by the State Administrative Court. However, the position of administrative efforts is only interpreted as a formality. This study aims to analiyz the position of administrative efforts in the settlement of state administration disputes and to find out how effective the administration efforts in reducing the number of state administration disputes in the State Administrative Courts in East Java. The results indicated that administrative efforts were the embodiment of the state law of Pancasila, but the effectiveness of administrative efforts in East Java was still very low or ineffective in reducing the number of state administrative disputes in the State Administrative Court.